Organization of independent work of students in the Moodle system - E. Yu. Zheleznіakova; I. V. Zmiyivs'ka (Academy of Cognitive and Natural Sciences, 2014)
Research goals: to study efficiency of interactive elements of Moodle system for students' independent work. Research objectives: to determine the basic possibility of introducing e-learning in the educational process of the country through the use of interactive elements of Moodle for organizing independent and individual work of students as an example of Kharkiv National Economic University named after Semyon Kuznets and Kharkiv Institute of Trade and Economics of Kyiv National University of Trade and Economics. Object of research: organization of independent work of students. Subject of research: the use of interactive elements of Moodle system for the organization of students' independent work. Research methods used: analysis of state standards and publications. Results of the research. We describe new forms of independent work by modern trends in Ukraine . The conditions of the scientific organization of independent work of students in higher education for quality training. Reviewed methodological value use of Internet technology for learning and teaching disciplines. The main conclusions and recommendations: for an effective use of Moodle to obtain qualitative knowledge in the learning process is necessary, we believe that the opportunity to create an effective information perception, understanding it for practical application.